O financiamento da política de assistência social no contexto do SUAS: tendências e particularidades do município do Natal-RN - Dantas, Maria Francisca Máximo (2011)
This dissertation analyzes the configuration of the financing of Social assistance in the municipality of Natal-RN in the context of their particular expressions of the problematizando municipal budget against neoliberal adjustment macroeconomic policy. The current trends of "disclaimer" and "desfinanciamento" of social protection by the State, in the context of contemporary capitalism, bring strong implications for Social Security, especially through the redirection of public resources to the international capital, which highlights the overlapping economic interests on social needs. Whereas the changes and innovations occurring in connection with the financing of Social assistance policy, the goal of this documentary research is to identify the characteristics and trends of funding this policy in Natal-RN, from the secondary data analysis from the City of Natal, the Ministry of Social development and hunger and Portal of transparency. In the light of the theoretical, research now presented, shows trends of investment in Social assistance in the municipality of Natal-RN, in the period 2005 to 2009, which are: the tiny role membership (08) Social assistance in the municipal budget; the dispersion and fragmentation of the resources of Social assistance in other organs and/or secretariats of municipal administration; the participation of just 47.5% in expenditure from own organ Manager; the low percentage of implementation of resources foreseen in the Annual Budget Laws; the low allocation of resources in Municipal Social Assistance Fund (FUMAS), which contradicts the national policy for Social Assistance-PNAS/2004; and the predominance of government transfers in the composition of the resources of Social assistance in the municipality. The results of this research suggest that the process of financing of Social assistance in Natal is distant from the principles and guidelines pointed by PNAS/2004. In addition to the effort to understand the complexity of the financing of Social assistance in Natal, this work seeks to contribute to a political analysis in the direction of strengthening social control and the struggle for the expansion of investment in social spending